Data Dashboard Acceptability, Use, and Perceived Effectiveness in Disseminating Local Overdose Data and Resources in a Rural New York State County: A Cross-Sectional Study - Zhongxuan He; Monika Salvage; Corinna A Noel (Online Journal of Public Health Informatics, 2025)
Abstract BackgroundIn 2023, Cayuga County, a rural county in New York State, developed and published a publicly available, interactive overdose dashboard highlighting demographic, geographic, and time trends in suspected overdoses as well as substance use–related resources in the community. Despite the widespread use of data dashboards in the overdose crisis, there is little evidence to suggest that these dashboards can effectively disseminate data and enable public health data-driven decision-making, especially in a rural county. We conducted an evaluation of the Cayuga County Overdose Data Dashboard to fill this knowledge gap. ObjectiveOur study aimed to evaluate the Cayuga County Overdose Data Dashboard’s acceptability, use, and perceived effectiveness in disseminating overdose data and resources. MethodsFollowing the launch of the dashboard, an online Qualtrics survey collected feedback from individuals older than 18 years of age living or working in Cayuga County, asking respondents to reflect upon their experience using the dashboard. The 10-minute survey assessed usage patterns and motivations to access the dashboard as well as the dashboard’s ease of use, most valued design features, and overall perceived effectiveness in communicating information on overdoses and local resources. Data were analyzed using descriptive statistics. ResultsFrom May to December 2023, a total of 61 individuals from Cayuga County completed the survey, including those with lived substance use experience (n=8, 13%) as well as their close contacts (n=28, 46%), health care providers (n=12, 20%), law enforcement (n=11, 18%), and local public health and mental health care professionals (n=27, 44%). The user-friendly design and frequent updates facilitate engagement, as 54% (n=33) of respondents reported accessing the dashboard at least monthly and 75% (n=46) using it to inform decision-making. Most thought that the dashboard was easy to use (n=59, 97%) and very effective in disseminating information (, 76%). From the 8 different types of overdose-related information portrayed on the dashboard, the most valued were the locations of treatment and recovery services, scoring an average of 4.75 (SD 0.65) on a 5-point scale (1=”Not important” to 5=”Most important”), followed by the locations of free, publicly accessible Naloxone (mean 4.58, SD 0.89) and trends in fatal and nonfatal overdoses (mean 4.48, SD 0.81). ConclusionsOverall, this study suggests that the Cayuga County Overdose Data Dashboard effectively disseminates information and enables data-driven decision-making in the region. When developing a community-level dashboard, our findings underscore the necessity of a user-friendly design, frequent data updates, and inclusion of key information and visuals on local overdose trends and resources.